Redox regulation of an AP-1-like transcription factor, YapA, in the fungal symbiont Epichloë festucae : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Genetics at Massey University, Manawatu, New Zealand - Cartwright, Gemma Maree (Massey University, 2013)
Reactive oxygen species (ROS) are emerging as important regulators required for the successful establishment and maintenance of the mutualistic association between the fungal endophyte Epichloë festucae and its grass host Lolium perenne (perennial ryegrass). The generation of reactive oxygen species (ROS) by the fungal NADPH oxidase, NoxA, has previously been shown to regulate hyphal growth of E. festucae in planta, a result that has led to the hypothesis that fungal-produced ROS are key second messengers in the symbiosis. However, the highly reactive nature of these molecules dictates that cells possess efficient redox sensing mechanisms to maintain ROS homeostasis and prevent oxidative damage to cellular components such as DNA, lipids and proteins. The Saccharomyces cerevisiae Gpx3-Yap1 and Schizosaccharomyces pombe Tpx1-Pap1, two-component H2O2 sensors, serve as model redox relays for coordinating the cellular response to ROS. While proteins related to the Yap1 and Pap1 basic-leucine zipper (bZIP) transcription factors have been identified in a number of filamentous fungi, the components involved in the upstream regulation remain unclear. This thesis presents an investigation into the role of the E. festucae Yap1 homologue, YapA, and putative upstream activators GpxC and TpxA, homologues of Gpx3 and Tpx1, respectively, in responding to ROS. YapA is involved in responding to ROS generated at the wound site following inoculation into ryegrass seedlings. However, deletion of yapA did not impair fungal colonisation of the host, indicating functional redundancy in systems used by E. festucae to sense and respond to plantproduced ROS. In culture, deletion of E. festucae yapA renders the mutants sensitive to only a subset of ROS and this sensitivity is influenced by the stage of fungal development. In contrast to the H2O2-sensitive phenotype widely reported for fungi lacking the Yap1-like protein, the E. festucae yapA mutant maintains wild-type mycelial resistance to H2O2 but conidia of the yapA mutant are sensitive to H2O2. Using a degron-tagged GFP-CL1 as a reporter, we found YapA is required for the expression of the spore-specific catalase, catA. Moreover, YapA is activated by H2O2, through disulfide bond formation, independently of both GpxC and TpxA, suggesting a novel mechanism of regulation exists in E. festucae. This work provides a comprehensive analysis of the role and regulation of the AP-1 transcription factor pathway in a filamentous fungal species.
Keywords: Epichloë; Genetics; Transcription factors